2021
DOI: 10.1016/j.ijpe.2020.107921
|View full text |Cite
|
Sign up to set email alerts
|

OR-methods for coping with the ripple effect in supply chains during COVID-19 pandemic: Managerial insights and research implications

Abstract: The COVID-19 pandemic unveils unforeseen and unprecedented fragilities in supply chains (SC). A primary stressor of SCs and their subsequent shocks derives from disruption propagation (i.e., the ripple effect) through related networks. In this paper, we conceptualize current state and future research directions on the ripple effect for pandemic context. We scrutinize the existing OR (Operational Research) studies published in international journals dealing with disruption propagation and structural dynamics in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
238
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 391 publications
(250 citation statements)
references
References 96 publications
9
238
0
3
Order By: Relevance
“…As a response to such issues, several studies suggested strategies for increasing upstream resilience. For example, Ivanov & Dolgui (2020a) proposed enhancing visibility by mapping supply networks, to predict potential disruptions and their consequences. This mapping can be useful for formulating node/supplier-specific strategies.…”
Section: Analyzing the Reviewed Articles On The Covid-19 Pandemic Inmentioning
confidence: 99%
See 1 more Smart Citation
“…As a response to such issues, several studies suggested strategies for increasing upstream resilience. For example, Ivanov & Dolgui (2020a) proposed enhancing visibility by mapping supply networks, to predict potential disruptions and their consequences. This mapping can be useful for formulating node/supplier-specific strategies.…”
Section: Analyzing the Reviewed Articles On The Covid-19 Pandemic Inmentioning
confidence: 99%
“…The scope of the challenges faced by these organizations largely depends on the severity of the outbreaks in question. A widespread public health incident such as an epidemic or pandemic can have substantial negative impacts on businesses and supply chains, including reducing their efficiency and performance ( Guan et al, 2020 , Ivanov, 2020a , Sodhi, 2016 ), and propagating disruptions across the supply chains (known as ripple effects) that affect their resilience and sustainability ( Ivanov, 2020b , Ivanov and Dolgui, 2020a ). Supply chains have encountered many severe disease outbreaks in the recent past; thus far, the World Health Organization (WHO) reported 1438 epidemics just between 2011 and 2018 ( Hudecheck et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We conducted a SCOPUS search based on the titles of the literature dealing with the ripple effect and in line with (Ivanov and Dolgui 2020c) as follows: (supply AND chain AND (ripple AND effect) OR (cascading AND failure) OR (risk AND transmission) OR (snowball AND effect) OR (risk AND propagation) OR (disruption AND propagation) OR (disturbance AND propagation) OR (structural AND dynamics). We limited the results to 'Business and Management', 'Engineering', and 'Decision Science' areas, and articles published in international journals.…”
mentioning
confidence: 99%
“…inventory and capacity buffers, backup sourcing, product substitution) Ma, He, and Gu (2020), Özçelik, Yılmaz, and Yeni (2020), Azaron, Venkatadri, and Doost (2020), Jahani et al (2020), Gholami-Zanjani et al (2020) Operative control level Reactive policy deployments for ripple effect control and recovery Choi (2020), Lee, Yoon, and Lee (2020) Table 1 provides an overview of the papers included in this special issue, their methodologies and major outcomes. In Table 2, the contributions shown in Table 1 are divided into a three-level structure following the classification proposed by Ivanov and Dolgui (2020c).…”
mentioning
confidence: 99%
“…Hence, for an emergency supply chain management, establishing models, defining roles along with responsibilities, and coordination across every tier of the chain is required, which is an overwhelming task for developing countries [ 20 ]. Recently, researchers have identified OR methods for containing the ripple effects generated by the COVID situation [ 21 ].…”
Section: Related Studymentioning
confidence: 99%